BUSINESS ANALYSIS IS A NEW DIRECTION OF ANALYTICAL WORK (Intent Research Scientific Journal, 2023)
This paper reveals the features of business analysis, taking into account the ongoing changes in the conditions of transformation of the domestic accounting system into international ones.